TAKIKARDIA SUPRAVENTRIKULAR PADA PASIEN USIA MUDA: “APA YANG BISA KITA LAKUKAN DI RUMAH SAKIT DAERAH?”: SUPRAVENTRICULAR TACHYCARDIA IN YOUNG AGED PATIENT :”WHAT CAN WE DO IN RURAL HOSPITAL?” - Salsa, Siti Tari; Saragih, Yusrina (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Supraventricular tachyarrhythmias are a group of heart rhythm disorders originating from the sinus node, atrial tissue, supplementary tissue, and junctional areas. A 19-year-old man was brought by his family to the emergency room of Muda Sedia Aceh Tamiang Hospital with complaints of heart palpitations that were felt 1 day before hospitalization accompanied by cold sweat. The patient had the same complaint 5 years ago and was taken to the clinic, and the patient said the complaint suddenly felt 2 years. History of lifting trade goods (+). Physical examination found that the patient was compos mentis, GCS 15 with a pulse frequency of 223x/minute. Supraventricular tachycardia (SVT) is a tachyarrhythmia that originates from or conducts through the atria or atrioventricular (AV) node. It occurs at heart rates greater than 100 beats/minute, The management of supraventricular tachyarrhythmias consists of acute and continuation phase management. Acute phase management is aimed at addressing hemodynamic emergencies, arrhythmia conversion and relief of clinical symptoms. Advanced supraventricular tachyarrhythmia management can be in the form of definitive therapy such as radiofrequency ablation or in the form of home therapy. Anamnesa and physical examination are very important for the management of supraventricular tachyarrhythmias. AbstrakTakiaritmia supraventrikular merupakan sekumpulan gangguan irama jantung yang berasal dari nodus sinus, jaringan atrium, jaringan suplementer, dan daerah junctional. Seorang laki-laki berusia 19 tahun dibawa oleh keluarganya ke IGD RSUD Muda Sedia Aceh Tamiang dengan keluhan jantung berdebar-debar yang dirasakan 1 hari SMRS disertai keringat dingin. Pasien mengalami keluhan yang sama 5 tahun yang lalu dan pernah berobat ke poliklinik, dan pasien mengatakan keluhan tersebut tiba-tiba dirasakan 2 tahun. Riwayat mengangkat barang dagangan (+). Pada pemeriksaan fisik didapatkan pasien sadar compos mentis, GCS 15 dengan frekuensi nadi 223x/menit. Takikardia supraventrikular (SVT) merupakan takiaritmia yang berasal dari atau dihantarkan melalui atrium atau nodus atrioventrikular (AV). Terjadi pada denyut jantung lebih dari 100 denyut/menit, Penatalaksanaan takiaritmia supraventrikular terdiri dari penatalaksanaan fase akut dan lanjutan. Penatalaksanaan fase akut ditujukan untuk mengatasi kegawatdaruratan hemodinamik, konversi aritmia, dan meredakan gejala klinis. Penatalaksanaan takiaritmia supraventrikular lanjut dapat berupa terapi definitif seperti ablasi frekuensi radio atau terapi di rumah. Anamnesis dan pemeriksaan fisik sangat penting untuk penatalaksanaan takiaritmia supraventrikular.